As ideias pedagógicas e a inovação na Primeira República brasileira : entre a tradução cultural e a gramática da escola - Silva, Débora Alfaro São Martinho da (2017)
This research aims to investigate the relation between pedagogical ideas and the innovation process of school education praxis. The objective is to comprehend how the process of production, appropriation and dissemination of pedagogical ideas is developed and how they articulate to school educational practice, by suggesting innovations with a view to apprehend the paradox of innovation and demystify the process of mythologizing the "new", to get closer to the practice as it is in classroom and, then, understand in a more concrete and entirely shape the school educational phenomenon. As theoretical-conceptual tools we admit the notions from the studies of "cultural translation", "hybridity" and "grammar of schooling", because they offer insights to understand the pedagogical ideas motives of traveling from their sites of origin, how they are apprehended at their arrival places, and how school educational practice articulates with innovation. All those process, when involving "cultural translation agents" and "authors of manuals”, which are responsible for translation of theories and practices from abroad into the national context and mediation of these to the school context - resulting in the study of intellectuals and their printed matter, admits the educational impressions of Carlos da Silveira and José Scaramelli as primary sources of investigation as the object of study. Intermediate intellectuals who would roam between the proposers (theoreticians) and the executors (teacher) acting as mediators and disseminators of the foreign pedagogical ideas in the country. Translated, in a literally and culturally way, in their forms, these pedagogical ideas were disclosed as theoretical-practical repertoire that was intended to instrument the teachers work in the classroom, and offered didactic and method which concentrate the innovation of educational practice and the revolution of the national school. Viewing such predicates, we could exam the pedagogical ideas in this work with a view to the apprehension of: what the authors present as "new" and whether the "new" they propose would be, as situated by both, different from what would already be placed in the school context and, capable of radically transforming the Brazilian school educational practice, establishing the other thing, which was until then, nonexistent. As categories of analysis, we delimit the conceptions of education and fundamentals of didactics and methodology, the latter being contrasted with prescriptions for the effectiveness of the teaching process, synthesized in the proposals of lessons and activities to be carried out by the teacher. Due to the production process of the “new” result from changes engendered in times of crisis, whose coexistence of temporalities accrues in the opening of fissures, it imposes other ways of thinking and providing the understanding and objectification of the existence conditions of present human life, giving the conditions for the emergence of the "new”. The First Brazilian Republic was established as a time frame for this research investigation object, since it comprises the intermission of time in which the bases of the Brazilian society are shaken because of the historical and social demands of in a time that imposes changes in its structure and relationships.